E-008 Microsurgical treatment of cerebral aneurysms after prior endovascular therapy: single center series and systematic review. (22nd July 2018) - Roy, A; Phillips, L; Howard, B; Barrow, D; Grossberg, J
Abstract : Background: Since its introduction in the early 90 s, endovascular treatment of cerebral aneurysms has had a steady upward trend and is the primary mode of treatment for most currently diagnosed cerebral aneurysms. Concurrently, the need for retreatment of cerebral aneurysms after prior endovascular treatment has also continued to grow, some of which can only be treated with microsurgical techniques. The factors that dictate outcomes in this group of patients are still not completely understood. Objective: To study factors contributing to patient outcomes after microsurgical treatment of aneurysms with prior endovascular treatment. Methods: Records were retrospectively reviewed for aneurysms treated after prior endovascular treatment. Demographics, treatment details and imaging were reviewed for all patients. A systematic review for these aneurysms was also conducted. Results: A total of 86 aneurysms were identified from the retrospective review. Mean age at the time of initial treatment was 50±12.42 years. Most patients initially presented with subarachnoid hemorrhage prior to initial endovascular treatment, with only 10 (13.70%) patients presenting with incidentally discovered lesions. mRS at discharge after initial treatment was good (0–3) in 81.4% of cases. Functional outcomes at the last known follow-up revealed a mRS of 0–3 in 71 (83.5%) patients. Only the maximum diameter of aneurysm was found to be a significant predictor of surgical complications (Wald χ 2 =5.72, p=0.0168) with an odds ratio of 1.84 (95% CI: 1.10, 2.93) for a 5 mm increase in maximum diameter. Systematic review identified 37 studies that were used to pool data on 370 total patients. Although type of surgery was identified as a predictor of poor outcomes this was significantly confounded by Hunt and Hess grade in the systematic review. Conclusion: Favorable outcomes can be obtained even for highly complex cerebral aneurysms that have failed endovascular treatment at high volume cerebrovascular centers. Initial presentation grade and aneurysm size are important predictors of final patient outcomes. Disclosures: A. Roy: None. L. Phillips: None. B. Howard: None. D. Barrow: None. J. Grossberg: 1; C; GRA. 4; C; NTI.